The role of ultrasound in controlling the glycine polymorphs - POLAT, SEVGİ (My University, 2022)
Glycine is the smallest protein-forming amino acid and is widely used in various fields owing to its many applications. The polymorphism phenomenon exhibited by glycine constitutes one of its advantageous properties. It has three polymorphs under atmospheric temperature and pressure, α, β, and γ, which are the most stable glycine polymorph, the metastable glycine polymorph, and the unstable polymorph of glycine, respectively. These different polymorphs affect the crystals' physical stability, solubility, density, melting point, and processability. Yet polymorphism is far from understood, and the means of controlling remains elusive. In the present study, we experimentally focus on how ultrasonic irradiation affects the polymorphic transformation of glycine. The resulting glycine crystals are characterized structurally by XRD and FTIR as well as morphologically and in terms of their surface charge. The experimental results indicate that ultrasonic irradiation and its intensity significantly affect the polymorphs and morphology, leading to the size variations of the glycine crystals. The agglomeration tendency under the working conditions was determined using aspect ratios obtained by dividing the crystal’s width by length. These results indicated that crystal agglomeration increased at higher ultrasonic power in terms of shape analyses, consistent with the images acquired from SEM analyses. To further understand the effect of ultrasonic irradiation on glycine polymorphs, these experiments were also performed in the presence of citric acid. It was found that the presence of the additive in the crystallization media caused the transition time to be extended; however, the presence of both the additive and ultrasonic irradiation lessened the polymorphic transformation time significantly.
Keywords: Polymorphism; glycine; morphology; ultrasound; shape analysis